Long-Term Course of Hypothyroidism Detected through Neonatal TSH Screening in a Population-Based Cohort of Very Preterm Infants Born at Less than 32 Weeks of Gestation - Birgit Odenwald; Aline Fischer; Wulf Röschinger; Bernhard Liebl; Heinrich Schmidt; Uta Nennstiel (International Journal of Neonatal Screening, 2021)
After several decades of successful newborn screening (NBS) for congenital hypothyroidism, the optimal hypothyroidism NBS algorithm for very preterm infants is still controversial. Due to concerns about an elevated risk of a false-negative initial thyroid-stimulation hormone (TSH) screening, repeat NBS has been implemented for this group. While transient hypothyroidism is known to be more frequent among very preterm infants, the prevalence of permanent hypothyroidism is generally assumed to be the same as in more mature newborns. This study analyses screening and long-term follow-up data from the population-based cohort of 51 infants born from 1999–2017 at less than 32 weeks of gestation and diagnosed with hypothyroidism after NBS in the German Federal State of Bavaria (total number of infants screened 2,107,864). Severe permanent hypothyroidism was always detected at initial TSH screening unless there was a known confounding factor. Cases detected by repeat screening after a negative initial screen most frequently proved to be transient, less frequently mild permanent, or a definitive diagnosis was not possible because of inadequate re-evaluation of the thyroid axis. The prevalence of both permanent and transient hypothyroidism was elevated compared to a cohort of children from the same region born at a higher gestational age. The results seem to support the need for the repeated NBS of very preterm infants. However, as the recommendation to treat mild hypothyroidism is not based on high quality evidence, important issues for future research include treatment outcome studies or even a general review of whether this diagnosis meets the screening criteria. Meanwhile, involving a paediatric endocrinologist in treatment decisions is crucial for optimising the benefit of hypothyroidism screening for this particularly vulnerable group.